Challenges faced by Indian self-initiated expatriates in the United Kingdom due to difference in work-culture and work-life balance - Dhamija, Krish (2022)
The dissertation would have not been completed without the help and encouragement of the people around me. I would like to show heartfelt gratitude to my teacher, families, friends as well as those professionals who participated in this study. First and most important, I would like to thank my dissertation supervisor and mentor Dr. Rani Thanacoody for enlightening and guiding me on how to carry out this dissertation while being patient with all my doubts and questions. In addition, she always encouraged me to strive for better. Secondly, I would like to thank my parents who supported me through all my highs and lows unconditionally throughout my degree. Finally, a big thanks to all the participants who took out time from their busy schedules for being a part of this research, without them, it would have not been possible. I am also thankful to my dearest friends who stood by me when I tested positive with covid-19 during the study.